IMPROVING THE POSITIVE COMPETENCE OF FUTURE INFORMATICS TEACHERS THROUGH MODERN INFORMATION TECHNOLOGIES - Xolmurodov Behzod Botir o‘g‘li (Bright Mind Publishing, 2025)
Currently, the process of digitization in education is progressing at a rapid pace. In particular, computer science teachers - as specialists who arm the future generation with digital knowledge - need to know modern IT tools and use them effectively. A teacher should not only be a provider of knowledge, but also a mentor who teaches students to think independently and find creative solutions. This requires the development of positive competence of the teacher. Interactive platforms, virtual laboratories, artificial intelligence-based educational programs and online resources allow computer science teachers to organize the learning process more effectively. In today's labor market, IT knowledge and digital competencies are considered one of the key skills. Future computer science teachers themselves must have knowledge and practical skills in this area. Therefore, this article is relevant.
Keywords: Technology, competence, informatics, digital literacy, interactive, innovative.